EFEKTIVITAS METODE PROBLEM BASED LEARNING DAN PENDIDIKAN KARAKTER DALAM MATA KULIAH STATISTIKA DASAR - Amalia Fitri (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
The  research objective  is obtain the  effectiveness  of  learning mathematics with  PBL method and learning  instrument  that  oriented  character  building better  than  common teaching  method  applied  in  the  class.  The  effectiveness  of  learning is  marked: a)  the achievement  of exhaustiveness indivudually  problem solving skill test exceed  for KKM and  classical completeness exceed  75%,  b)  motivation and learning  process  skill  has  a positive  effect on the  problem  solving skill,  c)  the  average of  problem  solving skill test experiment class is better than the control class. Based on the result of this research, it can be  concluded  that  learning mathematics with  PBL  method and learning  instrument  that oriented  character  building    better  than  common  teaching  method  applied  in  the  class. Thus,  to  improve    problem  solving  skill    on  elementary  statistic’s  learning  and other materials with  the same characteristics suggested PBL method with  learning instrument that oriented character building.Keywords : Learning, Character, Problem Solving